Virtual support groups among adoptive parents: Ideal for information seeking?. Issue 4 (2nd October 2019) - Miller, J. Jay; Cooley, Morgan; Niu, Chunling; Segress, Melissa; Fletcher, Jessica; Bowman, Karen; Littrell, Lindsay
Abstract: Despite the use of online support groups within areas of child welfare, namely postadoptive services, research in this area has not kept pace. This study examined adoptive parent perceptions of a virtual platform utilized for an online support group, and the impact of these perceptions on information seeking effectiveness. Overall, findings indicate that participants viewed the platform as usable, flexible, and congruent with fostering adequate participant interaction. Perceived group interaction, satisfaction with group membership, and perceived usefulness of the virtual platform were all significant predictors of information seeking effectiveness. Data from this study suggest that ample consideration should be given to the form and function of - virtual platforms use to administer support groups. Implications for practice and apposite area of future research are discussed.